THE USE OF SEXIST LANGUAGE IN DAGELAN ACCOUNT ON INSTAGRAM - Bunga Sri Rahayu; Meisuri (State University of Medan, 2015)
This study deals with the use of sexist language in Dagelanaccount on Instagram.The objectives of this study were to find out the dominat type of ambivalentsexsim and the most prominent gender discussed in Dagelanaccount. This studywas conducted by using descriptive qualitative method. The data were collectedfrom Dagelanaccount in Instagramby capturing some pictures that have captionsrelated to sexist language and then analyzed into two types of ambivalent sexismtheory, hostile sexism and benevolent sexism. The result showed that there were24 sentences related to hostile sexism and 26 sentences related to benevolentsexism. The using of benevolent sexism is the most dominant used inDagelanaccount and the most prominent gender discussed in Dagelanaccount isfemale in hostile sexism.